A Continuously Tunable Booster Optical Amplifier-Based Fiber Ring Laser Covering L and Extended L Bands. Issue 4 (3rd July 2020) - Qureshi, Khurram Karim
ABSTRACT: We propose and demonstrate a simple design of semiconductor fiber ring laser covering a broad tunable range, comprising L and extended L bands. The proposed laser can be continuously tuned over 54 nm from 1578 to 1632 nm with a total output power of around 5.2 dBm and having a side mode suppression ratio (SMSR) of around 55 dB by incorporating a Fabry Pérot tunable filter. The generated output is highly stable with power and wavelength fluctuations within 0.2 dB and 0.05 nm, respectively.